16-17 yaş grubunda 20. yüzyıl sanat akımlarının aktif öğrenme yöntemleriyle öğretimi: bir eylem araştırması - Korde, Nermin Yay (My University, 2017)
ÖZETÇok yönlü olan insan, eğitime gereksinim duyan bir varlıktır. Eğitim sayesinde her bireyde var olan kapasitenin tanınması, yönlendirilmesi ve gelişmesi mümkündür. İnsan eğitimi için başlıca bileşenlerden biri de elbette sanat eğitimidir. Sanat eğitiminin verimli şekilde gerçekleştirilebilmesi de günümüzdeki önemli sorunlardan biridir.

ABSTRACTBeing versatile, humankind is a creature who is in need of education. Thanks to education, it is possible to recognize, lead, and improve the capacities of the individuals. For the education of the individuals, art education is of course one of the fundamental elements. Carrying out a fertile and effective art education is one of the important problems of our time.The topic which is preferred as being among the 20th century art movements, is within the curriculum of visual arts lesson and the art movements which were taught to the students are within the program of 11th and 12th graders. Apart from these, some other art movements were included because they were considered as necessary. The art movements are introduced in detail in the study however, during the instructions the main points of them were presented to the learners with visuals so that they can keep them in their long term memories.
Keywords: 20. Yüzyıl Sanat Akımları; 20th Century Art Movements; Active Learning; Aktif Öğrenme Art; Art Education; Eğitim ve öğretim; Görsel sanatlar; Görsel sanatlar dersi; Güzel sanatlar; Sanat; Sanat Eğitimi; Sanat, Eğitim; Türkiye; Visual Arts; Visual Arts Lesson